Social perception on the image of the civil servant and his duties - Rus, Mihaela; Tasențe, Tănase; Sandu, Mihaela Luminita; Viju, Vasile-Daniel; Rus, Ciprian-Vasile (Technium Social Sciences Journal, 2022)
The status of civil servants both in Romania and in other countries is of great practical interest, but also of a theoretical interest, because for the fulfillment of obligations and rights, this depends to a large extent on respect for human rights in the relationship between administration and citizen. In a society, where many of its component parts are always in a form of transformation, it is unfair to consider that, and the administrative system does not take part in this process, on the contrary, we can say that, as many other components, for a whole, a slowing down of activity until its disappearance, or simply its non-existence, would be the first steps toward a collapse of society. With the implementation of new reforms in the public sector, the problem arises of increasing public confidence in the civil service in total and in its representatives - civil servants - in particular, this calls for ethical education measures for both existing and future officials. From the very beginning, future civil servants have the need to form and maintain a positive image as representatives of the state apparatus.